LINKAGES BETWEEN STOCK AND COMMODITY MARKETS: EVIDENCE FROM RUSSIA - Ronkainen, Joona (My University, 2018)
This study examines the short-term linkages between crude oil, steel and wheat with seven stock indices in the Russia stock market. The seven indices examined are: materials, banking, energy, minerals, metals and mining, oil and gas, and Russia 50. The linkages are examined in two different time periods: the period ranging from 2010 to 2012 and the period from 2016 to 2018. The aim of the study is to find possible supporting evidence on the financialization hypothesis of commodities, and the effect of financial crisis on the degree of connectivity between stocks and commodities. The degree of connectivity is measured through finding the ratio of statistically significant Granger causalities from the total amount of pairwise causality tests. The results indicate that the crisis-period of 2014 caused a decline in the degree of connectedness between commodities and Russian stock indices. Even though total degree of connectivity was decreased, a significant increase of linkages could be found between commodities and the banking sector.
Keywords: Financial crisis; crude oil; causality; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|